2013
DOI: 10.5812/ircmj.11540
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oral Tiazinidine Effects on [intraoperative] Hemodynamic Responses During Direct Laryngoscopy Under General Anesthesia

Abstract: BackgroundDirect laryngoscopy and tracheal intubation can result in blood pressure and heart rate increase which in turn may lead to myocardial ischemia, cerebral hemorrhage, and even death in susceptible patients. Tizanidine is α2-receptor agonists that suppresses central sympathetic system.ObjectivesThis study evaluates the effects of oral Tizanidine on hemodynamic responses during operations and aims to determine the appropriate Propofol dosage to maintain anesthesia under BIS monitoring.Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…We did observe lower heart rate in tizanidine patients at multiple time intervals of preoperative, intraoperative and postoperative period. Similar observations were seen by Tabari et al 17 with lower baseline variations of heart rate with tizanidine premedication group compared with placebo group. As compared with other alpha 2 agonists, 1,2,15,25 we did not observe episodes of severe bradycardia, hypotension, AV block, rebound hypertension requiring pharmacological correction which suggests tizanidine to be associated with stable haemodynamics.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We did observe lower heart rate in tizanidine patients at multiple time intervals of preoperative, intraoperative and postoperative period. Similar observations were seen by Tabari et al 17 with lower baseline variations of heart rate with tizanidine premedication group compared with placebo group. As compared with other alpha 2 agonists, 1,2,15,25 we did not observe episodes of severe bradycardia, hypotension, AV block, rebound hypertension requiring pharmacological correction which suggests tizanidine to be associated with stable haemodynamics.…”
Section: Discussionsupporting
confidence: 88%
“…Tabari and workers. 17 observed significantly lower propofol dose for anaesthesia maintainence with 4mg tizanidine premedication. With inhalational anaesthetics, Wajima et al 5 found that 4 mg tizanidine premedication reduced the MAC of sevoflurane by 18% in adults.…”
Section: Discussionmentioning
confidence: 78%
“…Since patients who have undergone orthognathic surgery receive intermaxillary fixation (IMF) with either wires or elastics for a 7-14 day period postoperatively, PONV can possibly cause aspiration of gastric contents and be extremely life-threatening 1, 2, 5, 8 . Tizanidine is a centrally active α 2 -agonist, which has proven clinically efficacious in managing muscle spasticity [12][13][14] . This medication is structurally similar to clonidine and also has sedative, antianxiety, and analgesic properties [12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Tizanidine is a centrally active α 2 -agonist, which has proven clinically efficacious in managing muscle spasticity [12][13][14] . This medication is structurally similar to clonidine and also has sedative, antianxiety, and analgesic properties [12][13][14][15][16][17] . Nevertheless, side-effects such as hypotension and bradycardia seem to be less severe when tizanidine is prescribed instead of clonidine 5,[12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation